Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - Chapter 1 Review Problem Set: 58



Work Step by Step

Substituting $x= -4 $ and $y= -6 $, the given expression, $ \dfrac{-3x+4y}{3x} ,$ evaluates to \begin{array}{l}\require{cancel} \dfrac{-3(-4)+4(-6)}{3(-4)} \\\\= \dfrac{12-24}{-12} \\\\= \dfrac{-12}{-12} \\\\= 1 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.